Examination of dendritic growth and microsegregation during solidification of Al–Li binary alloy using the phase-field simulation coupling CALPHAD data. (September 2021) - Chen, Qingqing; Zhang, Lu; Tang, Sai; Liang, Chaoping; Ma, Yunzhu; Liu, Wensheng
Abstract: Dendritic growth is one of the most important phenomena during the solidification of alloys. However, solute redistribution on the front of solid-liquid interface may result in nonuniform distribution of concentration between dendrite branches. This often causes microscopic segregation and undermines the properties of materials. In order to control the solidification microstructure of Al–Li alloy, we firstly need to understand in depth the morphological and concentration evolution during dendrite growth. Here, the KKS (S.G. Kim, W.T. Kim, T. Suzuki) phase-field model coupling CALPHAD data is employed. The dependences of the dendrite morphologies and growth kinetics on undercooling or initial solute concentration are qualitatively analyzed. Dendrite growth rate increases slowly when undercooling ΔT is approximately less than 25 °C, and steeply when ΔT>40 °C corresponding to the transition from diffusional dendrite growth into rapid solidification. Accordingly, the obtained morphologies change from dendrite into seaweed crystal. The increase of supersaturation influences dendrite growth similarly in terms of growth rate and morphology. Moreover, through simulation of columnar dendrites growth, we find that the microscopic segregation becomes more severely with decreasing undercooling, or increasing supersaturation. These results demonstrate the capability of the technology—phase-field simulation coupling to CALPHAD in the modelling of microstructure evolution during solidification of alloys. Graphical abstract: The equilibrium concentration of the solid phase ( c s ) and the liquid phase ( c L ) calculated by CALPHAD. By coupling KKS model with CALPHAD methodology, it is simulated the growth morphology of dendrite during solidification of Al-Li binary alloy. Image 1 Highlights: As the first attempt of modelling dendrite evolution in Al–Li binary alloy, our study successfully simulated the growth of dendrite by coupling KKS model with CALPHAD methodology. The growth morphology and segregation of single dendrite and columnar dendrites under different initial conditions was simulated. The model was validated by comparing solute distribution coefficient with equilibrium distribution coefficient.